Religious/spiritual coping in people with chronic kidney disease: a cross-sectional study. - Sena Tínel, Jéssica; Cristovam de Souza, Djenane; Costa de Santana, Joice Requião; Alencar Marinho, Christielle Lidianne (Revista Cuidarte)
Introduction: Chronic kidney disease (CKD) is considered a public health problem due to its high morbidity and mortality rates. Objective: To assess religious/spiritual coping in people with chronic kidney disease as a strategy for coping with the disease. Materials and Methods: This quantitative exploratory resea rch was conducted out in a hemodialysis clinic. The sample consisted of 100 people with chronic kidney disease, undergoing hemodialysis treatment. The study used a socioeconomic demographic questionnaire and the Religious/Spiritual Coping Scale. Results: Altogether, 100 people participated in the study, with a mean age of 55.6 years and predominantly male (58%). Among religious/spiritual coping variables (positive, negative, total), the mean value of total religious-spiritual coping was the highest. The means of positive and negative coping indicate that the former is more used. Patients whose religion was Candomblé had higher positive coping, whereas Evangelical patients had higher negative coping, and Spiritists had higher total coping. Discussion: Religious/spiritual coping in the study population was high, demonstrating its importance for coping with chronic kidney disease. Conclusion: The kidney patients who participated in this study were quite adept at using religious/spiritual coping expressively and positively, pointing out the importance of this practice in coping with kidney disease.